Developing a mental health research agenda for football referees. (18th August 2021) - Gorczynski, Paul; Webb, Tom
ABSTRACT: The mental health of football referees at amateur and elite levels has received very little research attention, with the majority of mental health research focused on players. Unfortunately, such a shallow research pool has resulted in a deficit of knowledge which prevents not only the understanding of mental health symptoms and disorders in this population but also the creation of evidence-based interventions. As such, the purpose of this commentary is twofold: 1) to outline the importance of why an epidemiological understanding of mental health symptoms and disorders amongst referees is necessary and desperately needed and 2) to discuss how such epidemiological research can be used to design, deliver, evaluate and disseminate evidence-based mental health interventions to football referees. We provide an overview of the behavioural epidemiology framework and how it may be used to guide and execute future research and intervention endeavours.